The Japanese steel industry: with an analysis of the U.S. steel import problem - Kawahito, Kiyoshi (New York: Praeger Publishers, 1972)
Gave a survey of the post war history of the Japanese steel industry, analyses facets of contemporary industry as production, labor cost etc
Bibliography: p. 195-203.
kjo 16/01/2019
Loans
Keywords: Steel industry and trade